2011
DOI: 10.1167/iovs.10-6262
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brimonidine on Retinal and Choroidal Neovascularization in a Mouse Model of Retinopathy of Prematurity and Laser-Treated Rats

Abstract: BRI treatment significantly attenuated vitreoretinal VEGF concentrations, retinal vascular leakage, and retinal and choroidal neovascularization in animal models of ROP and CNV. BRI may inhibit underlying event(s) of ischemia responsible for upregulation of vitreoretinal VEGF and thus reduce vascular leakage and retinal-choroidal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Clinical studies with brimonidine 0.33% gel report significant reductions in erythema on both clinician‐ and patient‐reported scales with maximal effect 3–6 hours after drug application . Brimonidine acts by selectively binding to α2‐adrenergic receptors present on smooth muscle in the peripheral vasculature, resulting in transient local vasoconstriction and other vascular effects (Table ). Other α2 receptor agonists have further demonstrated the ability to reduce neutrophil extravasation and inhibit PGE2 release …”
Section: Targeted Mechanisms Of Current Rosacea Therapeuticsmentioning
confidence: 99%
“…Clinical studies with brimonidine 0.33% gel report significant reductions in erythema on both clinician‐ and patient‐reported scales with maximal effect 3–6 hours after drug application . Brimonidine acts by selectively binding to α2‐adrenergic receptors present on smooth muscle in the peripheral vasculature, resulting in transient local vasoconstriction and other vascular effects (Table ). Other α2 receptor agonists have further demonstrated the ability to reduce neutrophil extravasation and inhibit PGE2 release …”
Section: Targeted Mechanisms Of Current Rosacea Therapeuticsmentioning
confidence: 99%
“…The brimonidine‐induced reduction of erythema and pain is presumably due to vasoconstriction combined with an anti‐inflammatory effect, possibly due to reduced release of mast cells . Existing literature furthermore show that brimonidine reduces the concentration of vascular endothelial growth factor and thus in perspective, application of brimonidine not only once after IPL but for a longer time period may potentially maintain telangiectasia reduction . In contrast to pharmacological studies, including one in vivo study in mice that showed a significant reduction in oedema after application of brimonidine, we only found a clinical trend in favor of brimonidine to reduce IPL‐induced oedema compared to air‐cooling alone .…”
Section: Discussionmentioning
confidence: 99%
“…OIR is characterized by two pathological phases: early vaso-obliteration and late retinal neovascularization [20,21]. At present, the study and treatment of OIR and ROP focus on the late phase and not on the early phase [22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%